Análisis del modelo económico de brasil durante el periodo 2003 - 2013 (2014)
This research describes the reality of Brazilian economic model during periods of Luiz Inacio da Silva and Dilma Rousseff, delving into the various policies to curb inflation which hit Brazil in past decades to restore macroeconomic stability and much needed. Its main approach is based on explaining the effects of the presidential transition in 2010 when Dilma Rousseff took power in Brazil and the relationship of this with the depth of the prospects for economic growth, rising unemployment, inflation and the reasons for the boiling of public discontent with the considerable amount of unmet need, considering the origins and rise of the processes of change and stabilization policies, through a process of improvement thereof developed by Luiz Inácio da Silva finally, the deterioration in the effectiveness of such policies when the presidential power rests with Dilma Rousseff. This query based on the authors who have dealt in the past or pieces of it in order to reach certain conclusions to facilitate the way to understand the rise of a nation with a view to becoming a world power, the scope of its regional leadership, new growth opportunities and has the potential threats in the process of development and transformation.